Manajemen Organisasi Remaja Masjid Nurul Jannah Prabumulih untuk Meningkatkan Partisipasi Remaja dalam Kegiatan Keagamaan - Okta Selfiyani; Achmad Syarifudin; Anang Walian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study is entitled "Management of Youth Organizations at the Nurul Jannah Prabumulih Mosque to Increase Youth Participation in Religious Activities". The purpose of this study was to determine the condition of the youth organization of the Nurul Jannah mosque in organizational management of religious activities at the Nurul Jannah mosque in Karang Jaya village, as well as the supporting and inhibiting factors for youth in the Karang Jaya village mosque. In this study the authors used a qualitative method with a descriptive approach. The data collection techniques of this research are observation, interviews and documentation. The theory used is organizational management theory. According to George R. Terry organizational management is the activity of planning (Planning), organizing (Organizing) mobilization (Actuating) and monitoring (Controling), where all of these activities aim to achieve organizational targets. The results of this study are that the management of youth organizations at the Nurul Jannah Prabumulih mosque can be considered good enough to participate in religious activities at the Nurul Jannah mosque. This is because the youth in Karang Jaya village still have the desire to participate, so they try to manage this organization as well as possible with their fellow members. As a form of youth management at the Nurul Jannah mosque to increase participation in religious activities, namely inviting fellow youth to participate in activities and be active in mosque youth organizations, improve communication among fellow members and start updating member performance. Looking at the supporting factors, namely religious teachings, the role of mosque administrators and the role of the local government so as to create a sense of togetherness and attractiveness in participating and the inhibiting factor is the lack of teenagers who have an interest in religious activities due to activities outside such as school and outside school. As for the researchers' suggestions for the government of Karang Jaya Village, namely village government institutions as input for the village head and other officials in Karang Jaya village, Prabumulih Timur District, to be able to provide responses and efforts to overcome various things that are inhibiting factors for the creation of inter-religious harmony in this village.